2022
DOI: 10.1039/d2sm00627h
|View full text |Cite
|
Sign up to set email alerts
|

A hydro-thermophoretic trap for microparticles near a gold-coated substrate

Abstract: Optical tweezers have revolutionised micromanipulation from physics and biology to material science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…It is also observed that the particle predominantly emits in a back-scattered direction (−z-direction, see the schematic in figure 3) and self-propels in the opposite direction due to the temperature gradient [35]. This absorption-induced motion can be thought to be an 'active' self-thermophoretic motion inside the optical trap with the tendency of the particle to move from hotter to colder region [40,41]. This will cause the particle to have a complex flow profile with a propulsion velocity, v which is given by [42,43]…”
Section: Theorymentioning
confidence: 98%
“…It is also observed that the particle predominantly emits in a back-scattered direction (−z-direction, see the schematic in figure 3) and self-propels in the opposite direction due to the temperature gradient [35]. This absorption-induced motion can be thought to be an 'active' self-thermophoretic motion inside the optical trap with the tendency of the particle to move from hotter to colder region [40,41]. This will cause the particle to have a complex flow profile with a propulsion velocity, v which is given by [42,43]…”
Section: Theorymentioning
confidence: 98%
“…A basic hydrothermal method [32] is followed to prepare the Fe-doped NaYF 4 :Yb,Er upconverting particles [21,28]. To prepare 15 at% Fe doped NaYF 4 :Yb,Er (Fe-15 NYF), 0.126 M yttrium nitrate (Y(NO 3 ) 3 ,63 at% of Y) and 0.3 M of sodium citrate (Na 3 C 6 H 5 O 7 ) were mixed with 14 ml of water by vigorous stirring for 10 min.…”
Section: Preparation Of Fe-doped Upconverting Particlesmentioning
confidence: 99%
“…The conventional magnetic hyperthermia technique employs alternating magnetic fields with frequencies in the order of hundreds of kilo-Hertz [24,25]. The precise control over the translations [26][27][28] and rotations [29][30][31],…”
Section: Introductionmentioning
confidence: 99%
“…In the past, people have demonstrated the indirect trapping of micro-objects by the controlled generation of pressure-driven fluidic environments or by employing potential energy landscapes and force fields generated by the temperature distributions in the particle-fluid neighborhood [ 21 23 ]. One such promising approach involves the use of hydro-thermophoretic traps [ 24 ], which can be used to trap and manipulate microparticles using a combination of fluid flow and temperature gradients.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrate the controlled, continuous rotation of a microparticle in roll sense, while being confined in a hydro-thermophoretic trap [ 24 ]. It is well known that heating a gold substrate can initiate the thermoplasmonic fluid flows, and also the temperature gradient on the same substrate can cause thermophoretic diffusion of the particle simultaneously [ 23 , 24 , 42 ].…”
Section: Introductionmentioning
confidence: 99%